Linker histone regulates the myeloid versus lymphoid bifurcation of multipotent hematopoietic stem and progenitors - Kutay Karatepe; Bruna Mafra de Faria; Jian Zhang; Xinyue Chen; Hugo Pinto; Dmitry Fyodorov; Esen Sefik; Michael A. Willcockson; Richard A. Flavell; Arthur I. Skoultchi; Shangqin Guo (Proceedings of the National Academy of Sciences, 2025)
Myeloid-biased differentiation of multipotent hematopoietic stem and progenitor cells (HSPCs) occurs with aging or exhaustion. The molecular mechanism(s) responsible for this fate bias remain unclear. Here, we report that linker histone regulates HSPC fate choice at the lymphoid versus myeloid bifurcation. Linker histones package nucleosomes and compact chromatin. HSPCs expressing a doxycycline (dox)-inducible H1.0 transgene favor the lymphoid fate, display strengthened nucleosome organization, and reduced chromatin accessibility at subsets of genomic regions. The genomic regions showing reduced chromatin accessibility host many known marker genes of myeloid-biased HSCs. The transcription factor Hlf is located in one of the most differentially closed regions, whose chromatin accessibility and gene expression are reduced in H1.0 high HSPCs. Failure to reduce Hlf expression in multipotential HSPCs abrogates the H1.0-endowed lymphoid potential. Furthermore, HSPCs display aspartyl protease–dependent H1.0 decreases, especially in response to interferon alpha (IFNα). Aspartyl protease inhibitors preserve endogenous H1.0 levels and promote the lymphoid fate of wild type HSPCs. Thus, our work elucidates a molecular scenario of how myeloid bias arises and uncovers a point of intervention for correcting myeloid skewed hematopoiesis.